Molecular approaches to uncover phage-lactic acid bacteria interactions in a model community simulating fermented beverages. (October 2022) - Ledormand, Pierre; Desmasures, Nathalie; Bernay, Benoit; Goux, Didier; Rué, Oliver; Midoux, Cédric; Monnet, Christophe; Dalmasso, Marion
Abstract: Food microbial diversity and fluxes during the fermentation processes are well studied whereas phages-bacteria interactions are still poorly described in the literature. This is especially true in fermented beverages, and especially in cider, which is an alcoholic fermented apple beverage. The transcriptomic and proteomic responses of the lactic acid bacterium (LAB) Liquorilactobacillus mali UCMA 16447 to a lytic infection by phage UCMA 21115, both isolated from cider, were investigated, in order to get a better understanding of phages-bacteria interactions in such fermented beverage. During phage infection, 122 and 215 genes were differentially expressed in L. mali UCMA 16447 strain at T15 and T60 respectively, when compared to the uninfected condition. The same trends were confirmed by the proteomic study, with a total of 28 differentially expressed proteins found at T60 . Overall, genes encoding cellular functions, such as carbohydrate metabolism, translation, and signal transduction, were downregulated, while genes involved in nucleotide metabolism and in the control of DNA integrity were upregulated in response to phage infection. This work also highlighted that phage infection repressed many genes involved in bacterial cell motility, and affected glycolysis. Highlights: The first lytic phage isolated from cider, targeting a L. mali strain, is described. Phage-bacteria interactions are studied within a model microbial community. Phage infection of L. mali impacts glycolysis and cell motility.